Construction of a 2D/2D heterojunction via integrating MoS2 on Co-doped g-C3N4 to improve photocatalytic hydrogen evolution under visible light irradiation. (8th July 2021) - Tian, Shaopeng; Ren, Huaping; Peng, Jianhong; Miao, Zongcheng
Abstract : Schematic of the photocatalytic mechanism of the MoS2 /CoCN-3 composite with enhanced photocatalytic properties for hydrogen evolution. Abstract : We successfully dispersed MoS2 on Co-doped g-C3 N4 nanosheets via a facile ultrasonic dispersion method to build a 2D/2D heterojunction in the present work. The structures of samples were investigated by characterization methods including TEM, SEM, XPS, and XRD, and the results clearly indicated that the Co species doped into the framework of bulk g-C3 N4 and MoS2 nanosheets were dispersed well on the 2D-CoCN sample. The photocatalytic activity of the MoS2 /CoCN-3 composite presents the optimum performance for hydrogen evolution of 54.1 μmol h −1, which is approximately 8.07 times that of the B-CN sample. The results of UV-vis spectra, PL spectra, time-resolved fluorescence decay spectra, etc. confirmed that the optimum performance for the hydrogen evolution of the MoS2 /CoCN-3 composites mainly results from the most visible light absorption, the largest specific surface area and the best efficiency of transferring charge carriers at the 2D/2D heterojunction. Furthermore, Co could partially replace C element in the g-C3 N4 framework and lead to carbocation formation. These carbocations facilitate the trapping of electrons and enhance the separation of photoproduced electron–hole pairs.